HTML, CSS, & JavaScript : all-in-one - McFedries, Paul (Hoboken, New Jersey : John Wiley & Sons, Inc., 2023)
Looking to start an exciting new career in front-end web building and design? Or maybe you just want to develop a new skill and create websites for fun. Whatever your reasons, it's never been easier to start learning how to build websites from scratch than with help from HTML, CSS, & JavaScript All-in-One For Dummies. This book has the essentials you need to wrap your head around the key ingredients of website design and creation. You'll learn to build attractive, useful, and easy-to-navigate websites by combining HTML, CSS, and JavaScript into fun and practical creations. Using the 6 books compiled within this comprehensive collection, you'll discover how to make static and dynamic websites, complete with intuitive layouts and cool animations. Web development is a fun, interesting, and challenging skill that can lead to a lucrative career (if you're so inclined).
Introduction -- Book 1: Getting Started -- Chapter 1: Getting Acquainted with HTML, CSS, and JavaScript -- Chapter 2: Getting Ready to Code -- Chapter 3: Finding and Setting Up a Web Host -- Chapter 4: Testing and Validating Your Code -- Book 2: Learning HTML Basics -- Chapter 1: Building Good Bones: Structuring the Page -- Chapter 2: Adding Links, Lists, and Other Text Tidbits -- Chapter 3: Working with Images, Video, and other Media -- Chapter 4: Building Tables with Your Bare Hands -- Chapter 5: Using Forms to Make a Page Interactive -- Chapter 6: Making Your Web Pages Accessible -- Book 3: Learning CSS Basics -- Chapter 1: Figuring Out the CSS Box Model -- Chapter 2: Getting to Know the CSS Selectors -- Chapter 3: Pseudo School: Learning Pseudo-Classes and Pseudo-Elements -- Chapter 4: Making CSS Make Sense -- Chapter 5: Taking the Measure of CSS -- Chapter 6: Fancifying Pages with Colors and Backgrounds -- Chapter 7: Taking Your Text Up a Notch with Web Typography -- Book 4: Building Dynamic Pages with JavaScript -- Chapter 1: JavaScript: The Bird$1 (Bs-Eye View -- Chapter 2: Understanding Variables -- Chapter 3: Building Expressions -- Chapter 4: Controlling the Flow of JavaScript -- Chapter 5: Harnessing the Power of Functions -- Chapter 6: Playing with the Document Object Model -- Chapter 7: Working with Arrays -- Chapter 8: Manipulating Strings, Dates, and Numbers -- Chapter 9: Storing User Data in the Browser -- Chapter 10: Debugging Your Code -- Chapter 11: Processing Form Data -- Book 5: Looking Good with Layouts -- Chapter 1: Exploring Some Layout Basics -- Chapter 2: Getting Fancy with Flexbox -- Chapter 3: Laying Out a Page with CSS Grid -- Chapter 4: Creating Responsive Layouts -- Index.s
Includes index.
Keywords: WEB SITES DESIGN; JAVASCRIPT (COMPUTER PROGRAM LANGUAGE)